Peranan Spiritual Quotient Terhadap Peningkatan Kinerja Perusahaan - Sujoko Winanto; Ahmad Maulidizen; Muhammad Rafi Thoriq; Amriatus Safaah (Peneliti.net, 2022)
Human resources are the most important aspect in forming an effective and efficient company performance. Human resources are the main determinants of the company's production process. By applying a human resource strategy that includes: job design, job analysis, and various related approaches and methods that can create a quality work ecosystem. In its application, good human resources are obtained with difficult achievements and costs that are expensive and difficult to maintain. Then the human resource strategy arrangement must be managed as well as possible to create a scope of work and work processes according to company goals. A good company is indicated by the happiness of the workers who are happy financially, mentally, and spiritually. Therefore, it is the responsibility of the company to provide the sufficiency of these factors. This article was compiled by collecting data from various credible literature, sourced and based on a conceptual understanding with a sprinkling of narrative science style language. The explanation of this article correlates with other articles, namely discussing the consolidation between humans and their place of work. Related descriptions of theories, ideas, problems, methods, solutions, application of human resources as capital and as individuals who are empowered in operations management. This article describes the structural procedures in human resource management with relevance to spiritual quotient (SQ).